Ideological attitudes predicting online hate speech: the differential effects of right-wing authoritarianism and social dominance orientation - Dellagiacoma, Laura; Geschke, Daniel; Rothmund, Tobias (Frontiers in Social Psychology, 2024)
While research on online hate speech (OHS) has expanded in recent years, only few studies adopt a theoretical framework to understand how ideological attitudes differently motivate individuals to engage with OHS. Drawing on the dual process motivational model of ideology by Duckitt and Sibley and on previous political psychological research on OHS, the goal of the present study was to investigate how individual levels of social dominance orientation (SDO) and right-wing authoritarianism (RWA) predict the odds of producing OHS for online platforms users. Logistic regressions were used to analyse data from a German representative online survey (N = 7,349). Our analyses indicate that SDO is related with higher odds of producing OHS, while RWA is related with lower odds of producing OHS. After adjusting for socio-economic factors and controlling for alternative predictors, the odd ratios remain significant, showing that these two ideological attitudes predict online hate speech in different directions.